Development of Story Book Learning Media in Grade IV on Theme 5 at SDN Mentaos - rofifah rofifah; Hawwin Fitra Raharja (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
Story books are media that attract children's attention because there children will be more interested in reading and understanding the story by using colorful pictures. This story book makes it easier for children to understand the contents of the story, especially books that discuss history if only described. Thematic books are very boring and unattractive and make children lazy to read them, so that there is a lack of understanding of the history of Indonesian heritage if children like to read interesting story books, children will easily understand about the history and create love for Indonesia, if the social studies material is class IV theme 5 sub-theme 1 is packaged with story book media, children will be happy to read it so that it fosters interest in reading so that students are interested in reading to the end. Story books are more personal as tools or media. The results of this study were obtained from material expert validators, media expert validators, and assessments from students